Image based analysis for assessing coastal water quality temporal and spatial variations in Limassol Harbor area in Cyprus - Papoutsa, Christiana; Retalis, Adrianos; Scoullos, Michael J.; Loizidou, Maria D.; Argyrou, Marina E.; Hadjimitsis, Diofantos G. (My University, 2013)
This study describes the spatial and temporal variations observed at the Limassol Harbor area covering a period of more than 25 years. All multi-date satellite imagery data used for this study acquired during the summer period, covering a period from May to August. The goal is to examine the temporal alterations been observed at the Limassol Harbor area during the years passed and the spatial variation according to the distance from the Harbor. Two areas were selected, one covering the area inside the Harbor and one other covering a larger area involving the area inside and outside the Limassol Harbor. Those two areas where cut off and water area was masked in order to indicate the differences observed. Temporal and spatial variations were apparent after applying unsupervised classification and stretching methods.
Keywords: Coastal water; Landsat ETM+ / TM; Satellite imagery; Spatial variations; Temporal variations; Water quality